2021
DOI: 10.1177/0885066621989959
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Barotrauma in Patients With Severe Coronavirus Disease 2019

Abstract: Objective.: To report the high incidence of barotrauma in critically ill patients admitted to the intensive care unit (ICU) with coronavirus disease 2019 (COVID-19) and to discuss its implications. Design.: Retrospective cohort study. Setting.: ICU of an academic county hospital in Los Angeles, CA admitted from March 15-June 20, 2020. Patients.: 77 patients with COVID-19 pneumonia. 75 patients met inclusion criteria. Results.: 21% of patients with severe COVID-19 sustained barotrauma (33% of patients receiving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
3
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 40 publications
(79 reference statements)
2
45
3
11
Order By: Relevance
“… 3 , 4 , 6 , 7 Similarly, a recent publication by Kahn et al demonstrated no difference in tidal volume or average/peak airway pressures in patients with COVID-19 receiving invasive mechanical ventilation between those with barotrauma and those without barotrauma. 21 While the underlying pathological mechanisms of PM or PTX in COVID-19 patients has yet to be fully elucidated, a widely postulated mechanism is that the severe and prolonged inflammation caused by the SARS-COV-2 virus leads to a widespread destruction of alveoli and airspace, increasing the likelihood of rupture with slight pressure changes from Valsalva maneuvers or mechanical ventilation. 22 , 23 These mechanisms may explain the possible increased incidence of barotrauma complications associated with mechanically ventilated COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 , 6 , 7 Similarly, a recent publication by Kahn et al demonstrated no difference in tidal volume or average/peak airway pressures in patients with COVID-19 receiving invasive mechanical ventilation between those with barotrauma and those without barotrauma. 21 While the underlying pathological mechanisms of PM or PTX in COVID-19 patients has yet to be fully elucidated, a widely postulated mechanism is that the severe and prolonged inflammation caused by the SARS-COV-2 virus leads to a widespread destruction of alveoli and airspace, increasing the likelihood of rupture with slight pressure changes from Valsalva maneuvers or mechanical ventilation. 22 , 23 These mechanisms may explain the possible increased incidence of barotrauma complications associated with mechanically ventilated COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 ARDS patients are thought to be indeed more vulnerable to PMD/PNX occurrence as compared with patients with ARDS due to other than COVID-19 causes [ 1 , 3 ]; a higher than expected incidence of PMD/PNX was also observed in COVID-19 patients not requiring invasive mechanical ventilation [ [3] , [4] , [5] , [6] ]. Furthermore, despite employment of lung protective ventilation strategies, these complications have difficult, non-standardized management, and are associated with increased risk of mortality [ 2 , 7 , 8 ]. Taken together, these findings corroborate the existence of a virus-induced frailty of airways tissue, resulting in an extensive, COVID-19-specific diffuse alveolar damage; microvascular thrombosis [ 9 ], interstitial inflammation, as well as endothelial barrier disruption have been suggested as main contributors for such a condition [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, among 160 randomly selected invasively ventilated COVID-19 patients without pneumothorax, mortality was 78/ 160 (49 %).We recently published a systematic review on rate of barotrauma among invasively ventilated COVID-19 patients [2]. Our pooled analysis included data from 13 studies and 1814 patients [3][4][5][6][7][8][9][10][11][12][13][14][15] and we found that pooled estimate of pneumothorax rate was 10.7 % (95 % confidence interval [CI] = 6.7 %-14.7 %), while overall rate of barotrauma event was 16.1 % (95 % CI = 11.8 %-20.4 %). In addition, we found an overall mortality rate for COVID-19 patients who developed barotrauma of 61.6 % (95 % CI = 50.2 %-73.0 %), as compared with a mortality of 49.5 % (95 % CI = 41.1 %-58.0 %) for COVID-19 patients who did not develop barotrauma.We are pleased to read that our findings are further reinforced by another study, that confirms that pneumothorax rate among mechanically ventilated COVID-19 patients is between 10 and 15 %.…”
mentioning
confidence: 99%
“…We recently published a systematic review on rate of barotrauma among invasively ventilated COVID-19 patients [2]. Our pooled analysis included data from 13 studies and 1814 patients [3][4][5][6][7][8][9][10][11][12][13][14][15] and we found that pooled estimate of pneumothorax rate was 10.7 % (95 % confidence interval [CI] = 6.7 %-14.7 %), while overall rate of barotrauma event was 16.1 % (95 % CI = 11.8 %-20.4 %). In addition, we found an overall mortality rate for COVID-19 patients who developed barotrauma of 61.6 % (95 % CI = 50.2 %-73.0 %), as compared with a mortality of 49.5 % (95 % CI = 41.1 %-58.0 %) for COVID-19 patients who did not develop barotrauma.…”
mentioning
confidence: 99%